The impact of work passion on work performance: the moderating role of P-O fit and meaningfulness of work - Ika Indriasari; Noni Setyorini (Department of Management | Faculty of Economics and Business | Universitas Diponegoro, 2018)
Our study aims to analyze the impact of auditor’s work passion on their performances, with meaningfulness of work and person organization fit (PO-fit) as moderating variables. Auditor, as a profession associated with assurance of compliance with their clients, highly requires good work passion to increase their spirit, avoid them from work saturation and improve their work quality. Therefore, our study expected that work passion positively affect work performance. Furthermore, meaningfulnes work and PO-fit were also expected to have moderating effect on the relationship of work passion on work performance. The results of regression and moderated regression analysis (MRA) on 87 samples collected from accoutants working in public accountant firm in Java, Indonesia, suggest that work passion has a positive effect on work performance. The result also shows that meaningfulnes was supported as a moderator on the relationship between work passion and work performance. However, our prediction that PO-fit could be a moderator in the effect of work passion on job performance of auditor was not supported.